2009
DOI: 10.1002/app.29434
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of composite membranes of polysulfone and microcrystalline cellulose

Abstract: in Wiley InterScience (www.interscience.wiley.com).ABSTRACT: Physical and chemical modifications of polymeric ultrafiltration membranes are necessary to improve their hydrophilic properties, strength, and other characteristics. Microcrystalline cellulose (MCC) was prepared from cellulose pulp by acid-catalyzed hydrolysis in the presence of ultrasonic radiation, and the properties of MCC were evaluated. Through the addition of MCC to a polysulfone (PS) membrane solution, a casting solution of a PS/MCC blend was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…RNSF with its very high surface area has plenty of hydroxyl and carboxylic functional groups at their surface which can attract the charged lime nanoparticles. Similar observation was found in previous work in case of using microcrystalline cellulose, cellulose nanocrystals or cellulose nanofibers isolated from bleached pulps when rejection of bovine serum albumin (BSA) was studied [25,27,36]. Although addition of cellulose nanocrystals or nanofibers to PSF resulted in increasing porosity and water flux, rejection of BSA (protein with charged surface) did not significantly affect by the increased porosity or water flux.…”
Section: Resultssupporting
confidence: 83%
“…RNSF with its very high surface area has plenty of hydroxyl and carboxylic functional groups at their surface which can attract the charged lime nanoparticles. Similar observation was found in previous work in case of using microcrystalline cellulose, cellulose nanocrystals or cellulose nanofibers isolated from bleached pulps when rejection of bovine serum albumin (BSA) was studied [25,27,36]. Although addition of cellulose nanocrystals or nanofibers to PSF resulted in increasing porosity and water flux, rejection of BSA (protein with charged surface) did not significantly affect by the increased porosity or water flux.…”
Section: Resultssupporting
confidence: 83%
“…The addition of cellulose fi bers in PSf membranes proposed and carried out by this study increased the permeate fl ux. Zhang et al [4] observed the same, though in their work the PSf membranes were prepared with the addition of MCC.…”
Section: Pure Water Permeate Fl Uxmentioning
confidence: 70%
“…When Zhang et al [4] modifi ed PSf membranes with the addition of MCC, a casting solution of PSf/MCC blend was obtained. MCC changed the morphological structure of the membranes, by good distribution of MCC in PSf composite membrane, and thereby changed their properties regarding pure water fl ux and bovine serum albumin (BSA) solution retention.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane porosity was tested according to the method described in the literature [26]. The membranes were weighed when wet and were later dried in an oven.…”
Section: Methodsmentioning
confidence: 99%